Heat capacity ratio and the best type of heat exchanger for geothermal water providing maximum heat transfer - Agra, Ozden; Erdem, Hasan Huseyin; Demir, Hakan; Atayilmaz, S. Ozgur; Teke, Ismail (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
Geothermal water is generally used for heating another fluid and therefore heat transfer between these fluids must be as high as possible. For heat exchangers, heat transfer per unit temperature difference and heat capacity is defined by effectiveness of heat exchanger (epsilon) and capacity ratio of hot and cold streams (Cr). Effectiveness of heat exchanger decreases as capacity ratio increases. Therefore, it is desired to maximize the multiplication of effectiveness and capacity ratio to maximize heat transfer. A new model was suggested for the determination of the heat capacity ratio that provides the maximum heat transfer and best type of heat exchanger. Maximum heat transfer occurs when capacity ratio is unity and therefore epsilon*Cr curves given as a function of NTU (number of transfer units) for Cr = 1 for various heat exchanger types. Also, the best type of heat exchanger giving maximum heat transfer can be determined using epsilon*Cr curves for geothermal applications. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Effectiveness; NTU (number of transfer units); Heat exchangers; Geothermal energy; GENETIC ALGORITHMS; DESIGN; OPTIMIZATION; COST; Thermodynamics; Energy & Fuels